Análise da composição centesimal da saúva cabeça-de-vidro (Atta leavigata) Smith 1858 - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2024)
Edible insects are important in the diet of some traditional populations and have been gaining prominence in haute cuisine, due to their eccentricity and palatability. The glass-headed saúva (Atta leavigata), whose indigenous name is sarai-wengyia, is usually consumed by the Sateré-Mawé ethnic group, and has a very pleasant aroma and flavor, but there is no information about its nutritional composition in the scientific literature. . This study aimed to analyze the proximate composition of the glass-headed sauva. The saúvas were collected in the Nossa Senhora de Nazaré community, in the municipality of Maués – AM., and were stored at -20 °C. The proximate composition was analyzed according to official analytical methods for food analysis. Proteins were determined by the Kjeldahl method, lipids by the Bligh-Dyer method, ash by incineration in a muffle furnace at 550 °C and moisture by drying in an oven at 105 °C, until constant weight. All analyzes were performed in triplicate and in wet weight. The moisture content found was high, corresponding to 57.1 ± 5.5 g/100 g. A high protein content (26.7 ± 0.5 g/100 g) was also found, higher than that of boiled chicken eggs and equivalent to meat foods and their derivatives. The ash content was also high, with an average of 17.3 ± 3.1 g/100 g, a value similar to that found in other insects, such as termites. Lipids were found in smaller quantities, corresponding to 3.0 ± 0.6 g/100 g. The saúva also presented significant results for macrominerals, such as phosphorus at a value of 3.5 ± 1.7 mg/100g. Sodium was found to be high. Calcium was found to be low at 0.3 ± 0.35. It is concluded that the saúva consumed by traditional pollution presented a very relevant nutritional value and could constitute an alternative for obtaining this food as the main or ingredient in the human diet.
Keywords: Formiga; Populações tradições; Amazônia; CIENCIAS DA SAUDE: NUTRICAO; .; .